Compression parameters of hexagonal boron nitride on direct compression mixture of microcrystalline cellulose and modified starch - UĞURLU, TİMUÇİN (TAYLOR & FRANCIS LTD, 2015)
The objective of this study was to investigate the effects of conventional lubricants including a new candidate lubricant hexagonal boron nitride (HBN)'' on direct compression powders. Lubricants such as magnesium stearate (MGST), glyceryl behenate, stearic acid, talc and polyethylene glycol(6000) were studied and tablets were manufactured on a single station instrumented tablet press. This study comprised the continuation of our previous one, so mixture of microcrystalline cellulose and modified starch was used as a master formula to evaluate effects of lubricants on pharmaceutical excipients that undergo complete plastic deformation without any fragmentation under compression pressure. Bulk and tapped densities, and Carr's index parameters were calculated for powders. Tensile strength, cohesion index, lower punch ejection force and lubricant effectiveness values were investigated for tablets. The deformation mechanisms of tablets were studied during compression from the Heckel plots with or without lubricant. MGST was found to be the most effective lubricant and HBN was found very close to it. HBN did not show a significant negative effect on the crushing strength and disintegration time of the tablets when we compared with MGST. Based on the Heckel plots at the level of 1%, formulation prepared with HBN showed the most pronounced plastic character.
Keywords: Cohesion index; direct compression; hexagonal boron nitride; lubricants; lubricant effectiveness; EXTERNAL LUBRICATION; MAGNESIUM STEARATE; POWDER COMPACTION; TABLET LUBRICANT; FACTORIAL DESIGN; FORMULATIONS; NANOTUBES